#TITLE_ALTERNATIVE# - ALRIANES BACHNAS (NIM 13203167), AHMAD
Multi Inputs Multi Outputs (MIMO) system is frequently used on various kind of industry. For instance, the heater plant on steam-gas power plant has two variables such as pressure and temperature. These two variables are dependently related. If the pressure is changed, then the temperature will change eventually, the same thing happens to pressure. So, if one of the variables had problem such as saturation, the whole process will gone wrong. Some unwanted effect like higher overshoot and longer steady state delay will happen at both outputs. These effects will then lead to system instability. But by using PI anti-windup, the saturation problem can be solved. This final project will implement PI anti-windup controller, and compare the result with the simulation to prove the implementation. The controller is implemented on eZdsp TMS320F2812 board to control Two Input Two Output (TITO) plant model. The TITO plant is approached by using reverse frame technique. As the result, the implementation shows that the TITO plant output result is the same as the discrete domain simulation result. The plant outputs will become more tolerant to saturation on its input, and the control system is proven to be stable.